Moving Forward, Looking Back The European Avant-garde and the Invention of Film Culture, 1919-1939 - Hagener, Malte (Film Culture in Transition, 2007)
This first critical overview of the European film avant-garde ushers in a new approach and creates its own subject. Arguing that a European perspective is the only way to understand the film avant-garde of the 1920s and 1930s, Hagener provides a much-needed summary of the theory and practice of the movement. This incisive study also pioneers a new approach to the alternative cinema network that sustained the avant-garde, paying particular attention to the emergence of screening clubs, film festivals, and archives. This title is available in the OAPEN Library - http://www.oapen.org.